A scalable and multibias parameter extraction method for a small‐signal GaN HEMT model. (16th April 2018) - Chen, Yongbo; Xu, Yuehang; Wang, Feng; Wang, Changsi; Wu, Qingzhi; Qiao, Shiyang; Yan, Bo; Xu, Ruimin
Abstract: In this paper, a scalable and multibias parameter extraction method for gallium nitride high electron mobility transistor small‐signal model has been proposed. The main advantage of this method is that the temperature‐dependent access resistances and nonlinear thermal resistance have been taken into account, which makes the extracted access resistances and intrinsic elements more physical and reliable at different bias conditions for various device dimensions. The new modeling method has been validated by comparing the simulated small‐signal S ‐parameters with the measured data over a wide range of frequency.